FUNGSI KEPATUHAN MAKSIM PRINSIP KESANTUNAN PADA KOMENTAR BERITA DI FANSPAGE FACEBOOK MERDEKA.COM - Qurratul - Aini; S. Sumarlam; D. Djatmika (Universitas Muhammadiyah Surakarta, 2018)
This article discusses about maxim compliance function of politeness principle in the Fanspage Facebook comments of online news Merdeka. Com. Data in form of utterances were collected from Fanspage Facebook Merdeka.Com with politic rubric 23rd- 24th September 2016. The result of this research shows that the utterances that keep the maxims of politeness principle are in form of assertive, directive and expressive. Assertive has 2 sub function, they are “declare and understand”. Directive has 5 sub functions, they are “question”, “advise”, “recommend”, “confirm” and “invite”. Expressive has 6 sub function, they are “giving congratulation”, “praise”, “regret”, “hope”, “be grateful” and “glad”.